(untitled) (ENTHYMEMA, 2023)
From a narratological point of view, metalepsis is defined as a transgression of the narrative hierarchy in which an entity belonging to a higher level finds itself acting at a lower level, and vice versa. This paper offers an analysis of metalepsis’s expressive functions and philosophical implications. It is primarily highlighted its power to illustrate – using the specific expressive means of literature – some of the deepest problems of thought. Indeed, the paradoxical level-crossing that characterizes metalepsis turns up in intellectual activities apparently located quite far from the territory of artistic and literary creation – such as logic, metaphysics, philosophy of language and psychoanalysis. Our goal is to demonstrate that metalepsis’s expressive potential goes far beyond the representation of the problematic relationship between fact and fiction, as the metaleptic structure narratively reproduces a series of mental operations performed by the thought every time it is looking for its own limits.